Čin a ne riječi ili što ih još vrag nije odnio (Dubrovačka trilogija, imperativ prošlosti i Vojnovićevo kategoričko Ne) - Rafolt, Leo (2002)
In this article author argues the problem of conservative ideologies fully present in Vojnović's dramatic triology, especially regarding issues like history, myth, concepts of modernism etc.
Projekt MZOS
HRV